Analysis of Student Perceptions of Project-Based Learning: A Case Study in Experimental Physics Course - Sutrio, Sutrio; Gunawan, Gunawan; Hikmawati, Hikmawati; Verawati, Ni Nyoman Sri Putu; Busyairi, Ahmad; Haslinda, Padia; Isnaini, Ahmad Hardyan (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2025)
The urgency of this research lies in the critical need to understand the effectiveness of Project-Based Learning (PjBL) within the context of the Experimental Physics course, particularly in responding to modern curricular demands that emphasize problem-solving and creativity. This study aims to analyze student perceptions of PjBL implementation, covering learning style profiles, learning experiences, challenges, support systems, and the impact on problem-solving abilities. Utilizing a quantitative approach with a descriptive design, data were collected through surveys administered to students enrolled in the Experimental Physics course. The results indicate that the majority of students (65.7%) possess a Kinesthetic learning style, which aligns strongly with PjBL characteristics that emphasize hands-on practical activities. Student perceptions were classified as highly positive, with the highest ratings observed in the aspects of enhanced creativity and the relevance of projects to real-world applications. An interesting finding highlights the presence of "productive struggle," where, although task difficulty was rated as challenging, students perceived this difficulty as highly instrumental in developing new skills. Regarding problem-solving abilities, students felt competent in procedural design and analysis; however, accurate data collection and hypothesis formulation were identified as areas with the lowest scores. It is concluded that while PjBL is effective in enhancing student competence, its implementation requires optimization through more intensive scaffolding regarding the technical aspects of data measurement and hypothesis formulation, alongside improved laboratory facility support.